Dkar chag 'phaṅ thaṅ ma - Rta rdo (Mi rigs dpe skrun khaṅ, 2003)
Tibetan Buddhist bibliographical catalog of canonical texts called ʾPhaṅ-thaṅ-ma and Mahāvyutpatti, Buddhist terminology in Sanskrit with Tibetan explanation
Keywords: Buddhist literature; Tibetan; Tibetan literature; Buddhism